Long-term impact of exposure to coalmine fire emitted PM2.5 on emergency ambulance attendances. (February 2022) - Broder, Jonathan C.; Gao, Caroline X.; Abramson, Michael J.; Wolfe, Rory; Dimitriadis, Christina; Ikin, Jillian; Sim, Malcolm R.; Del Monaco, Anthony; Johnston, Fay H.; Carroll, Matthew; Brown, David; Smith, Karen; et al.
Abstract: Background: Little is known about the long-term health effects of coalmine fire smoke exposure. The 2014 Hazelwood coalmine fire event in southeast Australia released smoke into surrounding areas for 6 weeks. Objectives: We aimed to investigate whether individual-level exposure to coalmine fire-related PM2.5 was associated with a long-term increase in ambulance attendances following a coalmine fire event. Methods: A total of 2223 residents from the most exposed town of Morwell were assessed for ambulance attendances after the Hazelwood event from April 1, 2014 to December 31, 2017. PM2.5 exposure was estimated for each individual using participant self-reported location diary data during the event and modelled PM2.5 concentrations. Recurrent event survival analysis was used to evaluate the relationship between PM2.5 exposure and ambulance attendances. Results: For each 10 μg/m 3 increase in mean coalmine fire-related PM2.5 exposure, there was a 10% (adjusted hazard ratio [HR]:1.10, 95%CI:1.03–1.17) increase in the overall risk of ambulance attendances within 3.5 years after the coalmine fire. Exposure to PM2.5 was also associated with increased risk of respiratory (HR: 1.21, 95%CI: 1.02–1.44) and cardiovascular (HR: 1.13, 95%CI: 1.01–1.28) related ambulance attendances. Conclusion: These results demonstrate that exposure to coalmine fire smoke during the Hazelwood event was associated with a long-term health risk post the fire event, specifically for respiratory and cardiovascular conditions. These findings are important for effective implementation of health care services following future extended coalmine fire PM2.5 events. Graphical abstract: Image 1 Highlights: This is first to evaluate the long-term health impact of prolonged coalmine fire on ambulance attendances in individual level data. Recurrent event survival analysis was used to evalute the impact of mine fire-related PM2.5 on long-term risk of ambulance attendances. Exposure to mire fire smoke was associated with increase in ambulance attendances, specifically for respiratory and cardiovascular conditions.